SESAR BARATLAUT - TENGGARA DI DAERAH MAMUJU DAN SEKITARNYA DAN HUBUNGANNYA DENGAN PEMBENTUKAN CEKUNGAN KARAMA - Sidarto Sidarto (Jurnal Geologi dan Sumberdaya Mineral, 2008)
There are four parallel-sided NW-SE trending faults, Budong-budong, Talondo, Keang and Adang Faults in Mamuju and surrounding area. In Early Tertiary, the faults are dextral fault; however the faults are sinistral fault in the MioceneÂPliocene tectonics. Karama Basin, situated between Budong-budong and Talondo faults consists of Eocene trangressive sedimentary rocks. It is presumed a step over basin of these faults in Early Tertiary. Keywords: Northwest - southeast faults, Karama basin, Mamuju